I am trying to determine the general solution to the equation $y''+f(x)y=0$, where $f(x):R \rightarrow R$. Naturally, I'm trying to use series to find the solution. This is what I have:

Assume $y$ can be written in the form:

$y=\sum_{n=0}^\infty a_n (x-x_0)^n$


$y'=\sum_{n=1}^\infty na_n (x-x_0)^{n-1}$


$y''=\sum_{n=2}^\infty n(n-1)a_n (x-x_0)^{n-2}=\sum_{n=0}^\infty (n+2)(n+1)a_{n+2} (x-x_0)^n$.

Thus, the differnetial equation becomes

$\sum_{n=0}^\infty (n+2)(n+1)a_{n+2} (x-x_0)^n+f(x)\sum_{n=0}^\infty a_n (x-x_0)^n=0$


$\sum_{n=0}^\infty \big[ (n+2)(n+1)a_{n+2} +f(x) a_n\big] (x-x_0)^n=0$

This can only be true for all $x$ if

$(n+2)(n+1)a_{n+2} +f(x) a_n=0$



The recurrence relations are then

$a_n=a_{2k}=\frac{(-1)^k}{(2k)!}f(x)^ka_0$ and $a_n=a_{2k+1}=\frac{(-1)^k}{(2k+1)!}f(x)^ka_1$


$y=a_0 \sum_{n=0}^\infty \frac{(-1)^n}{(2n)!}f(x)^n (x-x_0)^{2n}+a_1 \sum_{n=0}^\infty \frac{(-1)^n}{(2n+1)!}f(x)^n (x-x_0)^{2n+1}$

which can be rewritten as

$y=a_0 \cos(\sqrt {f(x)} (x-x_0)+a_1 \frac{(x-x_0) \sin(\sqrt{f(x)}(x-x_0)}{\sqrt{f(x)}(x-x_0)}$

This all seems fine to me. However, when I choose a function for $f(x)$, and I check to see if the left hand side of the differential equation actually does equal zero, I find it does not. Where am I going wrong?


Your $a_n$ depends on $x$, therefore your Ansatz is not a power series. In other words, if you do your ansatz you would have to derive $a_n$ as well. But then you would obtain a system of differential equations for $a_n$ which might be even harder to solve.

  • $\begingroup$ So, how would you suggest approaching this problem? $\endgroup$ – Ben Nov 20 '17 at 11:18
  • $\begingroup$ In this generality this problem is quite hard, so I don't know if there even exists a nice formula for a solution. If you write you equation as a system of first order differential equations you might be able to apply something like this en.wikipedia.org/wiki/Magnus_expansion, but to be honest, I don't really know. $\endgroup$ – humanStampedist Nov 20 '17 at 11:22

You also need to expand $f(x)$ into a power series $$f(x)=\sum_nc_n(-x_0)^n$$ and then apply the Cauchy product to the second term, $$ f(x)y(x)=\sum_n\sum_{m=0}^n c_ma_{n-m}(x-x_0)^n $$ so that the coefficient relations are $$ a_{n+2}=-\frac1{(n+1)(n+2)}\sum_{m=0}^n c_ma_{n-m} $$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.